Essential fish - Krekelberg, Alyssa; Arbour, Jessica (2022)
"This book examines Earth's fish, highlighting a diverse selection of 22 notable species from around the world. A blend of narrative text, authoritative nonfiction content, fact boxes, and vivid photos bring these amazing fish to life. Features include a glossary, online resources, source notes, and an index."--
Alligator gar -- Blue tang -- Channel catfish -- Clearnose skate -- Electric eel -- Foureye butterflyfish -- Giant manta ray -- Gray reef shark -- Great barracuda -- Great white shark -- Lake sturgeon -- Largemouth bass -- Mandarin fish -- Pacific hagfish -- Siamese fighting fish -- Silver lamprey -- Sockeye salmon -- South American lungfish -- Southern stingray -- Spot-fin porcupinefish -- Whale shark -- Yellowfin tuna -- Essential facts -- Fish around the world -- Glossary -- Additional resources.
Includes bibliographical references (page 106) and index.
8-12 years.
Grades 4-6.
Keywords: Fishes -- Juvenile literature